The influence of sugarcane pre‐harvest fire on hantavirus prevalence in Neotropical small mammals - Gheler‐Costa, Carla (2022)
The use of pre-harvest fire in sugarcane fields surprisingly results in an increase in the abundance of Neotropical Sigmodontinae rodents, which might carry hantavirus. By contrast, fire suspension induces a decline in rodents in the first 5 years. The present study aimed to evaluate the effect of sugarcane harvest regimes on hantavirus prevalence in wild rodents. Field collections were carried out on a sugarcane production area in Northeast S˜ao Paulo, which is responsible for 30% of the ethanol production in Brazil. A few years after pre-harvest fire suspension, a high prevalence of hantavirus was found in small rodents at lower population density, but apparently higher population growth rate. Differences in life cycle between the rodents and their predators may explain such density patterns, as small rodents can breed twice or even three times each year, whereas their predators usually breed only once a year. Similarly, the temporal dynamics of the predator–prey relationship suggests that hantavirus prevalence is related to small rodent’s population growth and not density. Only Akodon montensis, Calomys tener, and Necromys lasiurus contained immunoglobulin G antibodiesagainst the recombinant nucleoprotein of Araraquara orthohantavirus, a genotype of Andes orthohantavirus, with no interspecific variation in seroprevalence among these species. However, males presented higher prevalence rate than females, possibly due to a male-biased dispersal pattern and a higher frequency of antagonistic interactions. Governance measures to mitigate the role of small wild rodents on the emergence of hantavirus in agricultural landscapes dominated by sugarcane plantations should include the use of wildlife-friendly management techniques (e.g., to mitigate the mortality of the predators of small rodents), human capacity building concerning wildlife-related conflicts, and multifunctionality of agricultural landscapes. Future studies should prioritize the possible relationship between microhabitat structure and hantavirus prevalence in small rodents in agricultural landscapes dominated by sugarcane fields.